Hubungan pengetahuan dengan sikap ibu hamil tentang pelayanan Antenatal Care Terintegrasi - Indah Permatasari; Tri Sunarsih (Jurnal Cakrawala Promkes, 2019)
Developing countries have a serious health problem with maternal death and illness. The maternal mortality rate in Indonesia is 190 per 100,000 live births. Antenatal Care is a solution to reduce maternal and child mortality. Pregnant women are advised to carry out antenatal surveillance at least 4 times; once in trimester 1, once in trimester II, and twice in trimester III. Mlati II Sleman Health Center has met the target coverage for Visiting 1 (100%) and Visiting 4 (93.5%), but some pregnant women who examined did not know what Integrated Antenatal Care was. The purpose of this study was to determine the relationship of knowledge with attitudes of pregnant women about integrated antenatal care services at Mlati Sleman Public Health Center. The type of research used was a quantitative explanatory study type. The method used in the survey was a cross-sectional approach. The study was conducted at the Mlati II Health Center, Sleman, Yogyakarta. A total sample of 80 pregnant women TM II and TM III. The sampling technique uses purposive sampling. Test statistics with Kendall's Tau. There was no significant relationship between knowledge and attitudes of pregnant women regarding integrated antenatal care services at Mlati II Health Center Sleman Yogyakarta because integrated antenatal care has become a program so that pregnant women have been directed to follow it. The significance value is 0.457> ± (0.05) and the correlation value shows -0.075. Pregnant women should more routinely check pregnancy according to the 10 T standard. Health workers need to improve the quality of integrated antenatal care services, it is necessary to motivate pregnant women to read the Mother-Child Health book so that mothers can remember the information contained in the Mother-Child Health book.